1996
DOI: 10.1016/0926-6410(95)00039-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neuronal activity in the supplementary motor area and primary motor cortex

Abstract: Neuronal activity in the supplementary motor area (SMA) and primary motor cortex (MI) have been compared in many experiments during performance of many different motor tasks. On one hand, the activity in both areas may appear similar, especially when the motor task is simple. On the other hand, if the motor tasks are more demanding, neuronal activity in the SMA exhibits a variety of complex relationship to many different aspects of motor behavior, while the activity in MI is mostly related to execution of moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 76 publications
6
32
1
Order By: Relevance
“…On the storage side, the insular activation in the verbal learning task, and the SMA activation in the maze-learning task, may represent regions where specific information for the performance of the task is stored. SMA might be a likely candidate for the storage of the sequential (40,41) and͞or temporal aspects of a motor sequence (22,23). Alternatively, SMA and insula may represent regions controlling access to that information, which might be stored elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the storage side, the insular activation in the verbal learning task, and the SMA activation in the maze-learning task, may represent regions where specific information for the performance of the task is stored. SMA might be a likely candidate for the storage of the sequential (40,41) and͞or temporal aspects of a motor sequence (22,23). Alternatively, SMA and insula may represent regions controlling access to that information, which might be stored elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…These three conditions paralleled the Naive, Practiced, and Novel conditions of the verb generation task. A control condition (Square Fast), comparable to the simple reading task, was used as the basic control for this study [for more complete analysis, see van Mier et al (22,23)]. In the Square Fast condition, subjects traced the simple square design as quickly as possible.…”
Section: Practice Effects On Maze Tracingmentioning
confidence: 99%
“…2D . More recently, these regions have been given functional labels now adopted by Tanji and colleagues under the premise that these regions are functionally disw x tinct 69,161,162,173,254,255,277,279 . These labels have also been used to organize data from functional imaging w x experiments carried out on humans 204 .…”
Section: Multiple Sub-areas Of Monkey Dmfcmentioning
confidence: 99%
“…Numerous studies have suggested that the activity in motor areas during this period reflects preparation of movement (Kurata and Wise, 1988;Mitz et al, 1991;Tanji and Mushiake, 1996;Wise et al, 1998;Paz et al, 2003;Padoa-Schioppa et al, 2004).…”
Section: Premovement Variability and Motor Statesmentioning
confidence: 99%